Tingkat Kecemasan Masyarakat Menghadapi Pasien Covid-19 Yang Sembuh Dari Rumah Sakit - Ariani Sulistyorini; Anggita Mayasari (The Indonesian Journal of Health Science, 2021)
ABSTRACT Covid-19 (Corona Virus Disease) is a new type of infectious disease that causes symptoms of fever, weakness, cough, convulsions, diarrhea, and shortness of breath. These cases resulted in many people who were confirmed to have Covid-19 to be treated at the hospital, which caused the public to be anxious when receiving the return of Covid-19 patients who recovered from the hospital. Covid-19 patients will be discharged when they have recovered with criteria/conditions such as no fever, no cough/sore throat, no seizures, and no diarrhea. Anxiety is a response that is felt by a person in the form of worry or fear which is then followed by a physical sensation that causes an individual to feel a danger that appears and threatens. The purpose of the study was to determine the level of public anxiety in dealing with Covid-19 patients who recovered from the hospital.The research used a descriptive design, the number of population and a sample of 25 respondents with a total sampling technique of sampling. The variable in the research is the level of public anxiety facing Covid-19 patients who have recovered from the hospital. Data collection was carried out on 15-30 December 2020. The data collection instrument used a HARS (Hamilton Anxiety Rating Scale) questionnaire. Data analysis with percentage and interpreted quantitatively.The results of the study of 25 respondents showed that 2 respondents (8%) did not experience anxiety, 15 respondents (60%) experienced mild anxiety, 5 respondents (20%) experienced moderate anxiety, and 3 respondents (12%) experienced severe anxiety.This may be influenced by gender, age, last education, occupation, ever or not experiencing anxiety, having or not getting information about Covid-19, and sources of information.It is hoped that respondents can prevent and reduce the risk of anxiety, for example by taking deep breaths, always thinking positively, reducing excessive use of social media, creating a healthy lifestyle by maintaining a regular diet and exercising, getting enough sleep and always maintaining health protocols. . Health workers are expected to provide education to the public about Covid-19 so that people can easily understand any information so as to reduce the occurrence of anxiety in the community Keywords: Anxiety, Public, Covid-19 Patients, Recover, Hospital